Tortilla Flat Painting - Peggy Worthington-Best:::Creator::::::::::::
A photo of a painting of Danny screaming insults at the Sicilian fisherman. This appeared along with 16 other original paintings by the same artist in a special 1947 edition of Tortilla Flat. Original is hanging on wall in the Steinbeck Center. Peggy Worthington Best (20th Century) was active/lived in Massachusetts. She was a fine artist and an illustrator. One of her "students'' was Norman Rockwell, who attended Best's Stockbridge, Massachusetts Wednesday sketching classes.